Metal lithium negative electrode and preparation method thereof, and lithium secondary battery using the same

The electrochemical electroplating method forms a metal lithium negative electrode with a pore three-dimensional structure on the current collector of the lithium secondary battery, which solves dendrites and mechanical stress problems, extends the battery life and simplifies the process.

CN112956049BActive Publication Date: 2025-03-14POSCO HLDG INC +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN201980073729.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-11-08
Filing Date
2019-07-09
Publication Date
2025-03-14
Estimated Expiration
2039-07-09

AI Technical Summary

Technical Problem

When using metal lithium as the negative electrode material for lithium secondary batteries, dendrites and mechanical stresses are easily formed during charging and discharging, resulting in a shortening of the battery life.

Method used

The electrochemical method is used to form a metal lithium negative electrode with a three-dimensional structure with natural pores on the current collector through the electroplating process, avoiding additional additional processes, and controlling the plating current and time to adjust the thickness, porosity and particle size of the lithium.

Benefits of technology

It prevents dendrites from being generated during charging and discharging, reduces mechanical stress, extends battery life, simplifies the process and improves economic efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112956049B_ABST
    Figure CN112956049B_ABST
Patent Text Reader

Abstract

The present invention relates to a metal lithium negative electrode and a preparation method thereof, and a lithium secondary battery using the same. A metal lithium negative electrode can be provided, comprising: a current collector with a flat structure; and a negative electrode active material layer containing metal lithium located on the current collector, wherein the metal lithium has a concave-convex structure, and no dendrites exist on the surface of the metal lithium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a metal lithium negative electrode and a preparation method thereof, and a lithium secondary battery using the metal lithium negative electrode. Background Art

[0002] In order to realize low cost and high energy density of secondary batteries, it has been proposed to use a metal lithium electrode as a negative electrode of a lithium secondary battery.

[0003] When metallic lithium is used as the negative electrode material, there are the following problems: dendrites are formed during the charge and discharge process, causing electrical short circuits, and due to repeated contraction and expansion of the negative electrode material, the negative electrode will be subjected to mechanical stress and cracks will occur, thereby shortening the battery life.

[0004] In order to overcome this problem, attempts have been made to realize a lithium negative electrode material having a three-dimensional structure in order to ensure a free space for lithium growth and suppress the growth of dendrites during the charge and discharge process.

[0005] In Korean patent application KR10-2010-0114321, a patterned silicon substrate is used to form a three-dimensional negative electrode material structure, and lithium is grown only in the concave space to inhibit the growth of dendrites. However, this method requires advanced process technology and costs such as development, etching, and etching based on semiconductor process methods, so the efficiency is extremely low and not economical.

[0006] In Korean patent application KR10-2016-0085954, physical force is applied to the surface of metal lithium to deform the metal lithium, thereby forming a three-dimensional concave-convex structure. However, the interval between the concave and convex parts of the three-dimensional concave-convex structure that can be obtained by physical pressure is about tens to hundreds of μm, which is relatively wide, and the depth of the concave part is also about tens to hundreds of μm, which is relatively deep, so the accommodation space ensured by realizing the three-dimensional structure is also very limited. As a result, the increase in surface area is also very small, and the effect of reducing current density is not great, which is not effective in suppressing the generation of lithium dendrites mainly caused by high current.

[0007] In particular, in order to obtain the desired effect, deeper recesses are required, and for metallic lithium with a thickness of more than several hundred μm, the recesses and projections described above can be formed. However, the lithium actually used in high-energy-density metallic lithium batteries requires a thinner thickness of about 10 to 50 μm, so it is not easy to form such recesses and projections for thin-film lithium. Summary of the invention

[0008] To overcome the previous problems, it is ultimately necessary to be able to generate very small irregularities over the entire area of ​​a thin-film lithium electrode by a simple and efficient method.

[0009] To this end, the present invention intends to form a three-dimensional structure naturally having pores when lithium is formed on a current collector through an electroplating process using an electrochemical method without requiring any additional processing.

[0010] The thickness, porosity and particle size of lithium formed by electroplating can be arbitrarily adjusted by adjusting the size and time of the electroplating current, so it is easy to obtain metallic lithium with a film thickness of several μm to tens of μm.

[0011] An implementation example of the present invention provides a metallic lithium negative electrode, comprising: a current collector with a flat structure; and a negative electrode active material layer containing metallic lithium located on the current collector, wherein the metallic lithium has a concave-convex structure, and no dendrites exist on the surface of the metallic lithium.

[0012] Here, the dendrite refers to a particle in which the ratio of the length in one direction in which the particle length is relatively long to the length in a direction perpendicular to the one direction is 3 or more.

[0013] The formation of dendrites can be avoided by controlling the conditions of the electroplating process described later.

[0014] The metal lithium negative electrode may have pores accounting for 5 to 30% of the total area based on the plane projection area of ​​the metal lithium. The pores refer to the concave parts formed in the depth direction of the concave and convex parts when the metal lithium is viewed from above.

[0015] Such irregularities can be formed by controlling the electroplating conditions rather than by a physical method, and the porosity can be controlled.

[0016] The depth of the concavo-convex in the thickness direction may be 20 to 100% of the total thickness of the metal lithium. Moreover, the depth of at least one concavo-convex may be 20 to 50% of the total thickness of the metal lithium.

[0017] That is, among the concavo-convex portions, there may be concave portions in which no metal lithium is plated to the base surface of the current collector, or there may be concave portions in which metal lithium is plated partially from the base surface.

[0018] In the metal lithium, the interval between the concavoconvexities may be 5 to 100 μm. The interval is also a factor that can be controlled by the process conditions during electroplating. This will be described later in the specific embodiments.

[0019] The thickness of the metal lithium may be 1 to 100 μm. If the metal lithium is too thick, it is difficult to obtain a sufficient charging effect relative to the increase in battery thickness, and peeling problems may also occur. If the metal lithium is too thin, it may lead to a decrease in battery characteristics.

[0020] The metal lithium negative electrode may further include a film located on the surface of the negative electrode active material layer.

[0021] During the preparation of the negative electrode, the film is formed by the reaction between the electroplated metallic lithium and the electrolyte, and the thickness, composition and characteristics of the film can be controlled by adjusting the composition of the electrolyte used and the electroplating process conditions.

[0022] The thickness of the film may be, for example, 2 nm to 2 μm, more specifically, in the range of 10 nm to 500 nm.

[0023] If the thickness of the film on the surface of the negative electrode is too thick, the lithium ion conductivity is low and the interface resistance is high, which may reduce the charge and discharge characteristics when used in a battery. In addition, if the film thickness is too thin, the film may be easily lost during the process of applying the negative electrode of the embodiment to a battery.

[0024] Therefore, the film is preferably formed uniformly and densely on the entire surface of the negative electrode with a relatively thin thickness within the range satisfying the above-mentioned thickness range.

[0025] The film may be a Li-NCHO based ionic compound, a Li-PCHO based ionic compound, LiF or a combination thereof. As mentioned above, the composition of the film may be controlled by the additives of the electrolyte and the composition of the electrolyte.

[0026] As a specific example, the film includes a Li-NCHO-based ionic compound.

[0027] In this embodiment, during the process of pre-lithiation of the negative electrode by electroplating, the film including the Li-NCHO series ionic compound can be formed by adjusting the composition and content of the plating solution.

[0028] The Li-NCHO-based ionic compound may include Li-O, CN, CO, and CH bonds.

[0029] More specifically, the Li-NCHO-based ionic compound may include a compound represented by one of the following Chemical Formulas 1 and 2.

[0030] [Chemical formula 1]

[0031]

[0032] In Chemical Formula 1, R1 and R2 are CH m F 2-m (m is one of 0, 1, and 2),

[0033] A1 is

[0034] n1 is an integer from 1 to 10.

[0035] [Chemical formula 2]

[0036]

[0037] In Chemical Formula 2, R3 and R4 are CH m F 2-m (m is one of 0, 1, and 2),

[0038] A2 is

[0039] n2 is an integer from 1 to 10.

[0040] More specifically, for example, when lithium nitrate (LiNO3) is used as a nitrogen compound and a plating solution is used in which an appropriate amount of the lithium nitrate is added to an ether solvent, and the negative electrode is pre-lithiated through a pre-lithiation process, a film including the compound represented by Chemical Formula 1 or Chemical Formula 2 can be formed on the surface of the negative electrode.

[0041] In addition, the film may further include LiF in addition to the Li-NCHO-based ionic compound.

[0042] Current collectors are used to make electrical connections within the battery.

[0043] The current collector may be in the form of a film, but is not limited thereto. For example, the current collector may be in the form of a mesh, a foam, a rod, a wire, or a sheet woven from wires (fibers).

[0044] As the material of the current collector, a material having conductivity and limited reaction with lithium can be used. As the material of the current collector, for example, one of copper, nickel, titanium, stainless steel, gold, platinum, silver, tantalum, ruthenium and alloys thereof, a conductive polymer, and a composite fiber in which a conductive layer is coated on a non-conductive polymer, or a combination thereof can be used.

[0045] If the thickness of the collector is thick, the weight of the battery increases and the energy density of the battery decreases. If the thickness of the collector is thin, it may cause overheating and damage when working at high current, and may be damaged by tension during the battery preparation process. Therefore, the thickness of the collector can be in the range of 1μm to 50μm.

[0046] Another implementation example of the present invention provides a method for preparing a metallic lithium negative electrode, comprising: preparing a current collector immersed in an electrolyte and a lithium supply source opposite to the current collector; and applying current to the current collector and the lithium supply source to electroplate metallic lithium on the surface of the current collector. In the step of applying current to the current collector and the lithium supply source to electroplate metallic lithium on the surface of the current collector, the current application is carried out in two steps, wherein the current density value when the secondary current is applied is greater than the current density value when the primary current is applied.

[0047] Figure 1 Schematic diagram of a device for a metal lithium negative electrode in one embodiment of the present invention. Figure 1 As shown, after immersing both the current collector and the lithium supply source in the electrolyte, metallic lithium can be electroplated on the current collector by applying current.

[0048] At this time, the current applied twice can be controlled. Thus, metallic lithium with a concave-convex structure can be prepared. The specific experimental basis will be described later.

[0049] More specifically, the current density when the primary current is applied may be 0.2 to 0.8 mA / cm 2 .

[0050] The current density when the secondary current is applied can be 1-4 mA / cm 2 .

[0051] The secondary current may be applied for a longer time than the primary current.

[0052] The time for applying the primary current may be 1 to 4 hours, and the time for applying the secondary current may be 1 to 24 hours.

[0053] Such current density and current application time can be controlled according to the desired concavo-convex structure of the metal lithium.

[0054] As a supply source of lithium used in electroplating, not only metallic lithium but also an electrolyte solution in which a lithium salt is dissolved can be used.

[0055] The electrolyte may be prepared by dissolving a lithium salt in a non-aqueous solvent.

[0056] More specifically, the lithium salt may be LiCl, LiBr, LiI, LiCO3, LiNO3, LiFSI, LiTFSI, LiBF4, LiPF6, LiAsF6, LiClO4, LiN(SO2CF3)2, LiBOB or a combination thereof. Based on the overall electrolyte, the concentration of the lithium salt may be 0.1 to 3.0M.

[0057] More specifically, this embodiment is characterized in that the electrolyte includes the lithium salt and a nitrogen compound as at least one non-aqueous solvent.

[0058] The nitrogen compound may include, for example, one or more selected from lithium nitrate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethane sulfonimide, e-caprolactam, N-methyl-e-caprolactam, triethylamine and tributylamin.

[0059] Among the nitrogen compounds, at least one of lithium nitrate, lithium bisfluorosulfonyl imide, and lithium bis trifluoromethanesulfonimide may be used as the lithium salt.

[0060] Among the nitrogen-based compounds, at least one of e-caprolactam, N-methyl-e-caprolactam, triethylamine, and tributylamin may be used as the non-aqueous solvent.

[0061] In addition, considering the viscosity of the plating solution, a common non-aqueous solvent can be added as a solvent to the electrolyte. This is because if the viscosity of the electrolyte is too high, the mobility of lithium ions decreases, and the ion conductivity of the electrolyte decreases, so the time required for the pre-lithiation process increases, reducing productivity.

[0062] The solvent may include, for example, at least one selected from the group consisting of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethylmethyl carbonate, diethyl carbonate, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, and 1,3,5-trioxane.

[0063] Another implementation example of the present invention provides a lithium secondary battery, comprising: a positive electrode; a negative electrode; and an electrolyte located between the positive electrode and the negative electrode, wherein the negative electrode is the negative electrode of the aforementioned implementation example of the present invention.

[0064] Since the currently commonly used battery structures are all universal, the specific description of the positive electrode, negative electrode and electrolyte of the lithium secondary battery is omitted.

[0065] When lithium is formed on a current collector through an electroplating process using an electrochemical method, a metallic lithium negative electrode having a three-dimensional structure naturally having pores can be provided without any additional processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 Schematic diagram of a device for a metallic lithium negative electrode according to an embodiment of the present invention.

[0067] Figure 2 The figure shows the microstructure shape of the metal lithium surface controlled by Examples 1, 2 and 3.

[0068] Figure 3 The figures show the surface and cross-sectional microstructure of the metal lithium having a thickness of 100 μm formed in Example 4.

[0069] Figure 4 This is a surface photograph of metallic lithium formed in Comparative Example 1.

[0070] Figure 5 This is a surface photograph of metallic lithium formed in Comparative Example 2.

[0071] Figure 6This is a photograph of the surface of Example 2 subjected to image analysis in order to analyze the porosity.

[0072] Figure 7 The diagram is about a method for measuring the depth of the concavities and convexities generated by the electroplating process, that is, the distance in the thickness direction from the surface of the electroplated lithium.

[0073] Figure 8 and Fig. 9 A diagram showing a method for measuring the interval between projections and recesses generated by an electroplating process.

[0074] Fig.10 This is a graph showing the measured values ​​of the concave-convex interval using a scatter plot and a box plot.

[0075] Fig.11 The following are evaluation results of the charge and discharge performance of lithium secondary batteries using the metal lithium negative electrodes prepared in Examples 1, 2, 3, 4 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0076] The following is a detailed description of implementation examples of the present invention. However, these implementation examples are only provided as examples, and the present invention is not limited thereto, but is only limited by the scope of the appended claims.

[0077] When forming a thin film metal lithium negative electrode in order to achieve high energy density, the present invention intends to minimize the charge and discharge volume change by making the thin film metal lithium negative electrode have a three-dimensional concave-convex structure so that lithium is filled into the empty space during the charging process.

[0078] This can prevent stress from being generated due to volume changes during the charge and discharge process, and ultimately prevent cracks in the lithium negative electrode material caused by charge and discharge.

[0079] Furthermore, the present invention aims to form tiny three-dimensional concavities and convexities within a few μm to maximize the surface area of ​​the lithium negative electrode, reduce the actual current density applied during charging and discharging, and inhibit the formation of lithium dendrites occurring under high current.

[0080] Furthermore, in the past, in order to form a three-dimensional structure, additional projections and depressions were pre-formed on the copper foil of the current collector or a mesh or foam form was used. However, in the present invention, the current collector is not subjected to additional processing and a flat copper foil is directly used. This is not only price competitive in terms of economic efficiency, but also prevents the problem of dendrites being formed in empty space, and when the battery is realized, the battery has excellent charge and discharge performance.

[0081] During the electroplating, three-dimensional metallic lithium may be formed on one surface of the negative electrode current collector, or may be simultaneously formed on both surfaces of the negative electrode current collector, as required.

[0082] In order to adjust the thickness, particle size and porosity of the electroplated lithium, the desired three-dimensional structure is obtained by adjusting the size of the electroplating current, the application time, the current application method, etc.

[0083] Furthermore, by adjusting the composition and additives of the electroplating electrolyte, the formation of dendrites that may occur when applying high current when forming lithium using electrochemical methods is suppressed. This microstructural control of metallic lithium can form metallic lithium with both a porous structure and no dendrites on a flat current collector, a structure that cannot be obtained by conventional methods.

[0084] When the metal lithium and the current collector obtained by the above method are used as the negative electrode to realize the battery, the three-dimensional pore structure can ensure the space (Free space) that can accommodate the growth of lithium during the charge and discharge process, and solve the short circuit problem with the positive electrode caused by the growth of dendrites. In addition, since the volume change of the negative electrode material can be accommodated, even if the negative electrode material metal lithium repeatedly shrinks and expands during the charge and discharge process, the mechanical stress generated thereby can be eliminated, and cracks in the negative electrode material can be prevented, resulting in a longer battery life.

[0085] The following are examples and comparative examples of the present invention. However, the following examples are only examples of the present invention, and the present invention is not limited to the following examples.

[0086] Examples and Comparative Examples

[0087] (Example 1) Preparation of Porous Metal Lithium by Electroplating Process (Adjusting Electroplating Profile)

[0088] according to Figure 1 The method shown is to prepare thin film metallic lithium by electroplating process.

[0089] Regarding the preparation of the plating solution, 40% of LiFSI and 10% of lithium nitrate were added to 100% by weight of the plating solution, and 19% of a fluorine compound was added to 100% by weight of the plating solution to prepare the plating solution. A 500 μm thick metal lithium plate with a purity of 99.9% was extruded onto a copper collector plate (Cu plate) as a lithium supply source, and a 10 μm thick copper foil (Cu foil) with flat surfaces on both sides was used as a collector.

[0090] While the lithium supply source and the current collector are electrically insulated in the plating solution, a current is applied through a power supply device, with the lithium supply source and the current collector serving as the positive electrode (+) and the negative electrode (-), respectively, to form a metallic lithium layer on the surface of the current collector.

[0091] Regarding the current application method, the current was applied in two steps. The first step was 0.8 mA / cm 2The current density was applied for one hour, and the second step was 4 mA / cm 2 A current density of 1.500 Å was applied for one hour. A lithium thin film having a thickness of about 20 μm was prepared by the method described above.

[0092] (Example 2) Controlling porosity by adjusting electroplating distribution

[0093] Metal lithium was prepared by the same method as in Example 1.

[0094] At this time, the pores of the produced metal lithium and the concavo-convex structure formed by the pores are intended to be changed by adjusting the magnitude and time of the applied current.

[0095] Regarding the current application method, the current was applied in two steps. The first step was 0.4 mA / cm 2 The current density was applied for two hours, and the second step was 2 mA / cm 2 A current density of 1.500 Å was applied for one hour. A lithium thin film having a thickness of about 20 μm was prepared by the method described above.

[0096] (Example 3) Controlling porosity by adjusting electroplating distribution

[0097] Metal lithium was prepared by the same method as in Example 1.

[0098] At this time, the pores of the produced metal lithium and the concavo-convex structure formed by the pores are intended to be changed by adjusting the magnitude and time of the applied current.

[0099] Regarding the current application method, the current was applied in two steps. The first step was 0.2 mA / cm 2 The current density was applied for four hours, and the second step was 1 mA / cm 2 A current density of 1000 Å was applied for four hours. A lithium thin film having a thickness of about 20 μm was prepared by the method described above.

[0100] (Example 4) Controlling thickness by adjusting the plating distribution

[0101] Metal lithium was prepared by the same method as in Example 1.

[0102] At this time, the pores, concavo-convex structure and thickness of the produced metal lithium are changed by adjusting the magnitude and time of the applied current.

[0103] Regarding the current application method, the current was applied in two steps. The first step was 0.2 mA / cm 2 The current density was applied for one hour, and the second step was 1 mA / cm 2 A current density of 100 μm was applied for 24 hours. A lithium thin film having a thickness of about 100 μm was prepared by the method described above.

[0104] (Comparative Example 1) Effect of Porosity and Thickness on Plating Distribution

[0105] Metal lithium was prepared by the same method as in Example 1.

[0106] At this time, the pores, concavo-convex structure and thickness of the produced metal lithium are changed by adjusting the magnitude and time of the applied current.

[0107] Regarding the current application method, 2 mA / cm 2 A current density of 1.50 N was applied for 0.6 h to prepare a lithium thin film with a thickness of about 5 μm.

[0108] (Comparative Example 2) Effect of porosity on electroplating distribution

[0109] Metal lithium was prepared by the same method as in Example 1.

[0110] At this time, the pores of the produced metal lithium and the concavo-convex structure formed by the pores are intended to be changed by adjusting the magnitude and time of the applied current.

[0111] Regarding the current application method, 0.2 mA / cm 2 A current density of 1.50 N was applied for 24 h to prepare a lithium thin film with a thickness of about 20 μm.

[0112] Table 1 below is a table summarizing the electroplating conditions and results of the examples and comparative examples.

[0113]

Table 1

[0114]

[0115] Experimental example

[0116] Figure 2 The figure shows the microstructure shape of the metal lithium surface controlled by Examples 1, 2 and 3. The figure shows that in the metal lithium thin film with the same thickness of about 20 μm, microstructures with different porosities and different concavo-convex shapes based on the porosity are formed.

[0117] Figure 3 The figure shows the surface and cross-sectional microstructure of a metal lithium foil having a thickness of 100 μm formed by Example 4. The figure shows that although the thickness of the metal lithium is thick, a three-dimensional pore structure is formed without generating dendrites by adjusting the current and time factors of the electroplating process.

[0118] in addition, Figure 4 This is a diagram of Comparative Example 1, showing that the metal lithium formed by electroplating is lacking, the portion without metal lithium formed in the total area is wide, and the pore fraction is too high. In addition, a large number of dendrites are generated at the edge of the particle.

[0119] Figure 5 The figure of Comparative Example 2 shows that lithium plating is completely obtained in the entire area, and no pores are present in the microstructure, thereby no surface uneven structure is formed.

[0120] Figure 6 This is a photograph of the surface of Example 2 subjected to image analysis in order to analyze the porosity.

[0121] More specifically, in order to compare the pores generated by the electroplating process and the concavo-convex state based on the pores, as shown in FIG. Figure 6 As shown, image analysis was performed on each surface microstructure photograph to measure the fraction of pores in the total area.

[0122] The values ​​are shown in Table 2 below.

[0123]

Table 2

[0124] distinguish Porosity fraction (%) Example 1 21.3 Example 2 17.3 Example 3 6.9 Example 4 14.4 Comparative Example 1 45.8 Comparative Example 2 0.3

[0125] *For Examples and Comparative Examples produced by the electroplating process, the pore fraction based on the plane projection area is shown.

[0126] Figure 7 This is a diagram showing a method for measuring the depth of the unevenness generated by the electroplating process, that is, the distance in the thickness direction from the surface of the electroplated lithium. In the photograph of the cross section of the electroplated lithium, the total thickness of the lithium is assumed to be 100%, and the flat surface state is shown as 0%, the state where the concave part of the unevenness reaches half of the total thickness of the lithium is shown as 50%, and the state where the concave part of the unevenness reaches the copper collector is shown as 100%.

[0127] Table 3 below is a graph showing the minimum and maximum values ​​of the depths of the concavities and convexities other than the flat surface, regarding the examples and comparative examples produced by the electroplating process.

[0128] In Examples 1 to 4, the minimum depth of the concavities and convexities generated by the pores is 20 to 50% of the total thickness of lithium, and the maximum depth of the concavities and convexities is 100%, at which time the concave portion of the concavities and convexities reaches the copper current collector.

[0129] In Comparative Example 1, the maximum depth of the concavities and convexities was 100%, whereas the portion where the metal lithium was not formed in the total area was too wide, and the minimum depth of the concavities and convexities could not be measured in the remaining portion except the flat surface.

[0130] In Comparative Example 2, not only is the cross section extremely dense, but the number of concavities and convexities generated by pores is extremely small, and the maximum depth of the concavities and convexities is less than 10%.

[0131]

Table 3

[0132]

[0133] Figure 8 and Fig. 9 The diagram is a diagram of a method for measuring the interval between the concave and convex parts generated by the electroplating process. Figure 8 In order to measure the length defined by d1, d2, d3, etc., measure Fig. 9 Pores and interparticle distances between pores in the surface microstructure photograph shown.

[0134] Table 4 below is a table that summarizes the minimum, maximum, average, and median values ​​of the concave-convex spacing for the examples and comparative examples produced by the electroplating process. Fig.10 This is a graph showing the measured values ​​of the concave-convex interval using a scatter plot and a box plot.

[0135] Regarding the intervals of the generated concavoconvexities, in the conventional method of forming a three-dimensional structure by applying physical force, several hundred μm of metal lithium is deformed to form a wider interval of several tens to several hundred μm, while in Examples 1 to 4 of the present invention, a minute concavoconvex interval of about 10 to 100 μm can be formed when a lithium thin film of 20 to 100 μm thickness is formed. This is in good accordance with the fundamental purpose of forming a three-dimensional structure, that is, to ensure a minute space and to expand the surface area.

[0136] Comparing Examples 1, 2, and 3 having the same thickness, there is a tendency that the pore area gradually decreases and the interval between the concave and convex gradually increases from Example 1 to Example 3. In the case of Comparative Example 2, the density is very high and the interval between the concave and convex cannot be measured.

[0137]

Table 4

[0138]

[0139]

[0140] Fig.11 Evaluation results of the charge and discharge performance of lithium secondary batteries using the metal lithium negative electrodes prepared in Examples 1, 2, 3, and 4 and Comparative Examples 1 and 2 are shown.

[0141] The following Table 5 shows the results of evaluating the charge and discharge life based on 80% of the initial discharge capacity. Fig.11 As shown in Table 5, the charge and discharge performance of the embodiment having pores and a concavo-convex structure is greatly improved. This indicates that the structure formed by the present invention has the effect of suppressing the formation of lithium dendrites during the charge and discharge process and the effect of suppressing the cracking of the lithium electrode caused by the charge and discharge stress.

[0142] In addition, the reason why Example 4 exhibits very excellent charge and discharge performance is that, unlike the 20 μm thickness of the metal lithium in Examples 1, 2, and 3, the thickness of the metal lithium in Example 4 is 100 μm, which is relatively thick. Therefore, the effect of the present invention is also manifested by the effect caused by excessive lithium supply.

[0143]

Table 5

[0144] distinguish Charge and discharge life (times) Example 1 42 Example 2 41 Example 3 38 Example 4 88 Comparative Example 1 7 Comparative Example 2 26

[0145] When a lithium secondary battery is constructed using the metallic lithium with a porous three-dimensional concave-convex structure formed by the present invention as a negative electrode, lithium will fill the empty space during the charging process, thereby minimizing the volume change during the charging and discharging process, preventing the generation of stress caused by volume change, and ultimately preventing cracks in the lithium negative electrode material generated during charging and discharging.

[0146] Furthermore, the three-dimensional structure will increase the surface area of ​​the lithium negative electrode and reduce the actual current density applied during charging and discharging, thereby having the effect of suppressing the formation of lithium dendrites that may be generated during high current charging.

[0147] In particular, in the present invention, unlike the conventional case where a current collector is processed by an additional pre-process to form a three-dimensional structure, a flat current collector is directly used, thereby simplifying the process and achieving excellent economic effect.

[0148] The present invention is not limited to the above-mentioned embodiments, and can be prepared in various forms. Those skilled in the art of the present invention should understand that other specific forms can be adopted without changing the technical ideas or essential features of the present invention. Therefore, it should be understood that the above-mentioned embodiments are illustrative in all aspects, and not restrictive.

Claims

1. A metallic lithium negative electrode, comprising: A current collector having a flat structure; and a negative electrode active material layer containing metallic lithium located on the current collector, The metal lithium has a concave-convex structure, There are no dendrites on the surface of the metallic lithium. The dendrite refers to a particle in which the ratio of the length in one direction in which the particle length is relatively long to the length in a direction perpendicular to the one direction is 3 or more. Wherein, based on the plane projection area of ​​the metal lithium, the metal lithium negative electrode has pores accounting for 5 to 30% of the total area, The depth of the concavoconvex in the thickness direction is 20-100% of the total thickness of the metal lithium. In the metal lithium, the interval between the concavo-convex is 5 to 100 μm.

2. The metallic lithium negative electrode according to claim 1, wherein In the metal lithium, the depth of at least one concavo-convex portion is 20 to 50% of the total thickness of the metal lithium.

3. The metallic lithium negative electrode according to claim 1, wherein The thickness of the metal lithium is 1 to 100 μm. 4 . The metal lithium negative electrode according to claim 1 , further comprising a film located on the surface of the negative electrode active material layer.

5. The metallic lithium negative electrode according to claim 4, wherein: The film is a Li-NCHO-based ionic compound, a Li-PCHO-based ionic compound, LiF or a combination thereof.

6. A method for preparing a metallic lithium negative electrode according to claim 1, comprising: preparing a current collector immersed in an electrolyte and a lithium supply source facing the current collector; and applying electric current to the current collector and the lithium supply source to electroplate metallic lithium on the surface of the current collector, In the step of applying current to the current collector and the lithium supply source to electroplate metallic lithium on the surface of the current collector, the current application is performed in two steps, wherein the current density value during the secondary current application is greater than the current density value during the primary current application.

7. The method for preparing a metallic lithium negative electrode according to claim 6, wherein: The current density when the primary current is applied is 0.2-0.8 mA / cm 2 .

8. The method for preparing a metallic lithium negative electrode according to claim 6, wherein: The current density when the secondary current is applied is 1-4 mA / cm 2 .

9. The method for preparing a metallic lithium negative electrode according to claim 6, wherein: The secondary current is applied for a longer time than the primary current.

10. The method for preparing a metallic lithium negative electrode according to claim 9, wherein: The time for applying the primary current is 1 to 4 hours.

11. The method for preparing a metallic lithium negative electrode according to claim 9, wherein: The secondary current is applied for 1 to 24 hours.

12. A lithium secondary battery comprising: a positive electrode; a negative electrode; and an electrolyte located between the positive electrode and the negative electrode, wherein the negative electrode is the negative electrode according to claim 1.

Citation Information

Patent Citations

  • Digital content transaction-breakdown the method thereof

    KR1020100114321A

  • Pharmaceutical Composition for Treatment or Prevention of Bone Diseases Comprising Extract of Forsythiakoreana Nakai

    KR1020160085954A

  • Lithium metal anode, fabrication method thereof, and lithium secondary battery comprising same anode

    WO2018117547A1